Integrating Speech Recognition and NLP for Efficient Transcription Solutions - Drashti Mehta; Dr. Rocky Upadhyay; Krishna Jariwala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Speech recognition, an essential component of natural language processing (NLP), plays a pivotal role in enhancing communication and human-computer interaction. This paper reviews the advancements, challenges, and applications of speech recognition, natural language understanding (NLU), and chatbot technologies. Current speech recognition systems utilize techniques like Mel Frequency Cepstral Coefficients (MFCC) and Hidden Markov Models (HMM) to address linguistic errors, gender recognition failures, and inaccurate voice recognition. Applications such as voice assistants offer continuous interaction capabilities, enabling users, including those with disabilities, to perform tasks like web searches and document preparation. Additionally, we examine vulnerabilities in voice assistants, particularly in NLU components like Intent Classifiers, which can misinterpret user inputs and pose security risks. The transformative impact of deep neural networks (DNN) on speech recognition since 2010 is also discussed, alongside their application to fields like machine translation and image captioning. Furthermore, this paper highlights the evolution of chatbots, integrating NLU platforms like Google DialogFlow and IBM Watson, to deliver intelligent, adaptive interactions. By addressing challenges in intent recognition and system integration, this review underscores the potential of AI-driven solutions to revolutionize speech-based applications.